(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article contains a critical analysis and results of several political reforms that have been carried out at the national level in recent years, reflecting the experiences of foreign countries, and coverage of several areas that are undergoing changes as a result of these reforms, including changes in the field of digital economy. and opinions about the results are expressed. This article is relevant in that it reflects the analysis based on the political arguments of recent years